Effects of Antimelanosis Agents on Quality and Shelf-life of Tropical Brackish Water Shrimp (Penaeus notialis) during Storage at 0°C and 7°C - Dabadé, D. Sylvain; HOUNHOUIGAN, DJIDJOHO JOSEPH; AZOKPOTA, PAULIN; NAGO KOUKOUBOU, HOUEFFA EUNICE SOREL (My University, 2020)
Tropical brackish water shrimp (Penaeus notialis) is an important commercial species in West Africa. Sulfiting agents, which may pose a risk to human health, are still intensively used to prevent melanosis in P. notialis. In this study, the effectiveness of a generally recognized as safe (GRAS) chemical product (4-hexylresorcinol (4-HR)) and a plant phenolic compound (catechin) in preventing shrimp spoilage was assessed. Freshly caught shrimps were treated with three 4-HR concentrations (0.005%, 0.01%, and 0.1%) and three catechin concentrations (0.05%, 0.1%, and 0.2%) and stored at 0°C and 7°C. Shrimp samples treated with sodium metabisulphite (1.25%) and untreated samples were used as positive and negative controls, respectively. At appropriate time intervals, samples were taken for microbiological, chemical, and sensory analysis. Total volatile basic nitrogen (TVBN) data were used to validate a previously developed model that predicts TVBN production in P. notialis. At 0°C, 4-HR, even at the lowest concentration, significantly (P < .05) inhibited melanosis formation. Catechin (0.2%) significantly lowered melanosis formation in P. notialis during the first two days of storage at 7°C. At 0°C, 4-HR treatments extended shrimp sensory rejection time by one week; while at 7°C, only a slight (<1 day) prolongation of sensory rejection time was noticed.
Keywords: 4-hexylresorcinol; catechin; modeling; TVBN; Penaeus notialis